LOCAL WISDOM-BASED CHARACTER EDUCATION AS AN EFFORT TO ESTABLISH STUDENT WITH SPECIAL NEEDS CHARACTER - Izul Islamudin; Hariyanto Hariyanto; Miftahul Alimin; M Risdamuddin Nurjanah (Fakultas Tarbiyah, Universitas Ibrahimy, 2023)
This study aims to describe the application of local wisdom-based character education as well as the supporting and inhibiting factors at SDLB Negeri Kedungkandang Malang City. The research method used is qualitative research with descriptive research type. Collecting data using observation techniques, interviews, and documentation. The process of data analysis through data collection, data reduction, data presentation, and draw conclusions. The results showed that the application of character education based on local wisdom for children with special needs was effective, explored the potential of students, instilled character values, and supported the process of growth and development of students both in cognitive, affective and psychomotor aspects. The supporting factors are the school principal, student guardians who really support its implementation, and the facilities and infrastructure are very supportive. Inhibiting factors, there are no significant inhibiting factors because the facilities are adequate. It's just that the teacher who teaches art has one teacher.